ARIA pharmacy 2018 "Allergic rhinitis care pathways for community pharmacy": AIRWAYS ICPs initiative (European Innovation Partnership on Active and Healthy Ageing, DG CONNECT and DG Santé) POLLAR (Impact of Air POLLution on Asthma and Rhinitis) GARD Demonstration project - Bosnic-Anticevich, Sinthia; Costa, Elisio; Menditto, Enrica; Lourenço, Olga; Novellino, Ettore; Bialek, Slawomir; Briedis, Vitalis; Buonaiuto, Roland; Chrystyn, Henry; Cvetkovski, Biljana; Di Capua, Stefania; Kritikos, Vicky; et al. (Allergy, 2019)
Pharmacists are trusted health care professionals. Many patients use over-the-counter (OTC) medications and are seen by pharmacists who are the initial point of contact for allergic rhinitis management in most countries. The role of pharmacists in integrated care pathways (ICPs) for allergic diseases is important. This paper builds on existing studies and provides tools intended to help pharmacists provide optimal advice/interventions/strategies to patients with rhinitis. The Allergic Rhinitis and its Impact on Asthma (ARIA)-pharmacy ICP includes a diagnostic questionnaire specifically focusing attention on key symptoms and markers of the disease, a systematic Diagnosis Guide (including differential diagnoses), and a simple flowchart with proposed treatment for rhinitis and asthma multimorbidity. Key prompts for referral within the ICP are included. The use of technology is critical to enhance the management of allergic rhinitis. However, the ARIA-pharmacy ICP should be adapted to local healthcare environments/situations as regional (national) differences exist in pharmacy care.
Keywords: veřejné zdravotnické služby; Disease Management; Pharmacists; lékárny; určení symptomu; Humans; kritické cesty; Rhinitis, Allergic; Pharmacies; Symptom Assessment; Telemedicine; role odborníka; Community Health Services; Professional Role; Public Health Surveillance; farmaceuti; ochrana veřejného zdraví; management nemoci; alergická rýma; adherence k farmakoterapii; telemedicína; Decision Support Systems, Clinical; lidé; Medication Adherence; Critical Pathways; systémy pro podporu klinického rozhodování